PEMBELAJARAN JARINGAN LOKAL SEBAGAI UPAYA MENINGKATKAN KETERAMPILAN SISWA DI SMK IBRAHIMY 1 SUKOREJO SITUBONDO - Zaehol Fatah; Rahmat Syarifuddin Chairil Anwar (Jurnal Padamu Negeri, 2026)
One of the biggest problems in technical education is that vocational students lack practical experience installing local area networks, especially when it comes to IP subnetting and UTP cable crimping. By using a project-based learning strategy with a direct practice approach, this study seeks to improve learner capabilities. The research was carried out at SMK Ibrahimy 1 Sukorejo Situbondo involving 32 students as participants. A classroom action research methodology was employed, encompassing phases of planning, implementation, observation, and reflection. Findings revealed that students' subnetting abilities improved by 63% (from 52.5 to 85.6) while UTP crimping skills increased by 95% (from 45.3 to 88.4) following two instructional cycles. Per-indicator analysis showed that color sequence arrangement experienced the highest improvement (from score 2.1 to 3.5), while cable cutting remained the biggest challenge. The study concludes that practical-oriented local network instruction significantly boosts students' vocational competencies